A high-fidelity physical map of human chromosome 21q in yeast artificial chromosomes. - Korenberg, J R; Chen, X N; Mitchell, S; Fannin, S; Gerwehr, S; Cohen, D; Chumakov, I (Genome Research, 1995)
Understanding of the human genome has been advanced significantly by the development of large DNA fragment libraries. To create a map of chromosome 21q that integrates the physical, cytogenetic, and linkage maps, we have characterized a subset of 127 chromosome 21 yeast artificial chromosome (YAC) clones for size, by pulsed field gel electrophoresis, for chimerism and cytogenetic location, by fluorescence in situ hybridization (FISH), and for sequence-tagged sites (STS) content, by PCR. It was found that 54% generated unique map locations on chromosome 21, and 45% detected sites on other chromosomes, of which 33% likely represented true chimerism. Using a simple algorithm, the data from nonchimeric clones have been combined to generate a size-corrected minimal tiling pathway including 58 chromosome 21q YACs that represent approximately 33 Mb and include 9 gaps. To confirm the resulting order and relationship to the cytogenetic map, the breakpoints from 23 cell lines partially aneuploid for chromosome 21 have been analyzed by quantitative Southern blot dosage analysis and FISH with a subset of the markers. As one way of investigating the relationship of the genetic to the physical map, the genetic map was superimposed on the physical map using a subset of well-defined markers common to both. The results suggest potential hot spots for recombination and/or gaps in the physical map. This integrated map will facilitate the search for the genes responsible for the Down syndrome phenotypes and provide a better understanding of genome organization and chromosome structure.